1991
DOI: 10.1172/jci115447
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial leukocyte adhesion molecule-1 mediates antigen-induced acute airway inflammation and late-phase airway obstruction in monkeys.

Abstract: This study examines the role of endothelial leukocyte adhesion molecule-i in the development of the acute airway inflammation (cell influx) and late-phase airway obstruction in a primate model of extrinsic asthma. In animals sensitive to antigen, a single inhalation exposure induced the rapid expression of ELAM-1 (6 h) exclusively on vascular endothelium that correlated with the influx of neutrophils into the lungs and the onset of late-phase airway obstruction. In contrast, basal levels of ICAM-1 was constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
76
0
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(77 citation statements)
references
References 26 publications
0
76
0
1
Order By: Relevance
“…First, this edema is not likely secondary to endothelial injury mediated by antibody-dependent cell-mediated cytotoxicity mechanisms in that F(ab')2 fragments of murine antibodies were used for all in vivo infusions. Secondly, in other animal studies using murine antibodies to E-selectin, similar observations were not described (25,56,57). Thirdly, we cannot be certain that increased vascular permeability occurred in animals treated with murine antibodies since precise kinetic and quantitative assessments of vascular leakage were not performed.…”
Section: Discussionmentioning
confidence: 66%
“…First, this edema is not likely secondary to endothelial injury mediated by antibody-dependent cell-mediated cytotoxicity mechanisms in that F(ab')2 fragments of murine antibodies were used for all in vivo infusions. Secondly, in other animal studies using murine antibodies to E-selectin, similar observations were not described (25,56,57). Thirdly, we cannot be certain that increased vascular permeability occurred in animals treated with murine antibodies since precise kinetic and quantitative assessments of vascular leakage were not performed.…”
Section: Discussionmentioning
confidence: 66%
“…In an acute challenge model, an anti-human E-selectin mAb (CL2, 2 mg/kg, i.v.) was found to block the late bronchial response (56). This protection was associated with a reduction in leukocyte, specifically in neutrophil, infiltration into the lung.…”
Section: Discussionmentioning
confidence: 85%
“…In previous studies of allergic inflammation in the mouse, ICAM1/LFA-1, very late Ag-4/VCAM1, and P-selectin have been implicated in the development of both peribronchial inflammation and airway hyperreactivity (9 -13). Additionally, early primate studies showed that blockade of E-selectin also reduced allergic pulmonary inflammation (8). Finally, increased expression of the E-and P-selectins has been observed in asthmatic patients (14 -17), suggesting that these molecules are up-regulated in human disease and may contribute to the alteration of pathophysiology.…”
mentioning
confidence: 99%
“…Chemokines produced locally then promote the arrest of leukocytes on the lumenal surface and their migration into surrounding tissues. Both adhesion receptor-dependent and independent recruitment pathways have been identified in lung inflammation (5)(6)(7)(8). In previous studies of allergic inflammation in the mouse, ICAM1/LFA-1, very late Ag-4/VCAM1, and P-selectin have been implicated in the development of both peribronchial inflammation and airway hyperreactivity (9 -13).…”
mentioning
confidence: 99%